A case of apogeotropic horizontal canal benign paroxysmal positional vertigo (cupulolithiasis) due to head contusion in an adolescent - Atsushi Tamura; Michiya Satoh (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
A 17-year-old high school boy who complained of severe positional vertigo visited our hospital. He belonged to an American football team in high school, and his head often hit opponents during games. The vertigo was strongest when his left ear was down in the supine position. Physical examination and computed tomography revealed no abnormalities. However, positional testing revealed apogeotropic direction-changing horizontal nystagmus. Rightward nystagmus in the left-ear-down supine position was stronger than leftward nystagmus in the right-ear-down supine position. Additionally, in the supine position, a null point for horizontal nystagmus was identified, beyond which the nystagmus changed direction. This null point was evident when the head was turned 10 degrees to the side. The diagnosis was right lateral canal type of BPPV caused by cupulolithiasis. He was treated with the Gufoni maneuver and reported a decreased incidence of positional vertigo upon re-evaluation.